Bladder and bowel dysfunction in Down syndrome with neural tube defect: case report and review of the literature - Roberta Onesimo; Cristiana Agazzi; Luca Massimi; Valentina Giorgio; Chiara Leoni; Giuseppe Zampino; Claudia Rendeli (BMC, 2023)
Abstract Background Down syndrome is a genetic disorder caused by trisomy of chromosome 21 and characterized by an increased risk of multiorgan involvement. In Down syndrome children, functional constipation and lower urinary tract infections have been described, together with higher risk for incontinence and delayed sphincter control. At present, to our knowledge, no clear association between Down syndrome, Bladder Bowel Dysfunction and neural tube defects has been previously described. Case presentation We describe two female patients with Down syndrome presenting Bladder Bowel Dysfunction in association with neural tube defects, who both underwent personalized multidisciplinary intervention and pelvic floor rehabilitation, with good clinical outcomes. Conclusion At present, no screening program has been established in order to rule out neural tube defects or neurogenic urinary anomalies in Down syndrome patients presenting bowel and/or bladder dysfunction. In our opinion, presence of spinal abnormalities, despite rare, may be contribute to urinary symptoms and should be ruled out in patients presenting progressive or persistent Bladder Bowel Dysfunction. Early diagnosis and management of spinal cord defects associated with neurogenic urinary dysfunction may allow to prevent possible complications.